35.2k views
5 votes
Solve the equation -3h + 6 = -15 for h.

User Bpirvu
by
4.6k points

2 Answers

2 votes

Answer:

h = 7

Explanation:

-3h + 6 = -15

Get rid of the 6 by subtracting it from both sides.

-3h + 6 - 6 = -15 - 6

-3h = -21

Get rid of the -3 by dividing it from both sides.

-3h/-3 = -21/-3

h = 7

User MiffTheFox
by
5.8k points
5 votes


\huge\textsf{Hey there!}


\textsf{-3h + 6 = -15}


\large\text{SUBTRACT 6 to BOTH SIDES}


\textsf{-3h + 6 - 6= -15 - 6}\\\\\\\large\text{CANCEL out: 6 - 6 because that gives you 0}\\\\\large\text{KEEP: -15 - 6 because that helps you solve for the h-value}\\\\\textsf{-15 - 6 = \bf -21}


\large\text{New equation: -3h = -21}


\large\text{DIVIDE -3 to BOTH SIDES}\\\\\mathsf{(-3h)/(-3)=(-21)/(-3)}\\\\\\\large\text{CANCEL out: }\mathsf{(-3)/(-3)}\large\text{ because that gives you 1}\\\\\\\large\text{KEEP: }\mathsf{(-21)/(-3)}\large\text{ because that solves for your h-value}


\mathsf{h = (-21)/(-3)}\\\\\\\mathsf{(-21)/(-3)=\bf 7}\\\\\\\\\mathsf{h = \bf 7}


\boxed{\boxed{\large\textsf{Answer: \huge\bf h = 7}}}\huge\checkmark


\large\text{Good luck on your assignment and enjoy your day!}

~
\frak{Amphitrite1040:)}